Release and swelling studies of an innovative antidiabetic-bile acid microencapsulated formulation, as a novel targeted therapy for diabetes treatment - Mooranian, Armin; Negrulj, Rebecca; Al-Sallami, H.; Fang, Zhongxiang; Mikov, M.; Golocorbin-Kon, S.; Fakhoury, M.; Arfuso, Frank; Al-Salami, Hani (Informa Healthcare, 2015)
In previous studies carried out in our laboratory, a bile acid formulation exerted a hypoglycaemic effect in a rat model of type 1 diabetes (T1D). When the antidiabetic drug gliclazide was added to the bile acid, it augmented the hypoglycaemic effect. In a recent study, we designed a new formulation of gliclazide–deoxycholic acid (G-DCA), with good structural properties, excipient compatibility and which exhibited pseudoplastic–thixotropic characteristics. The aim of this study is to test the slow release and pH controlled properties of this new formulation. The aim is also to examine the effect of DCA on G release kinetics at various pH values and different temperatures. Microencapsulation was carried out using our Buchi-based microencapsulating system developed in our laboratory. Using sodium alginate (SA) polymer, both formulations were prepared including: G-SA (control) and G-DCA-SA (test) at a constant ratio (1:3:30), respectively. Microcapsules were examined for efficiency, size, release kinetics, stability and swelling studies at pH 1.5, 3, 7.4 and 7.8 and temperatures of 25 °C and 37 °C. The new formulation is further optimised by the addition of DCA. DCA reduced bead-swelling of the microcapsules at pH 7.8 and 3 at 25 °C and 37 °C, and even though bead size remains similar after DCA addition, the percentage of G release was enhanced at high pH values (pH 7.4 and 7.8, p < 0.01). The new formulation exhibits colon-targeted delivery and the addition of DCA prolonged G release suggesting its suitability for the sustained and targeted delivery of G and DCA to the lower intestine.